2017
DOI: 10.7554/elife.20994
|View full text |Cite
|
Sign up to set email alerts
|

Nkx2.5 marks angioblasts that contribute to hemogenic endothelium of the endocardium and dorsal aorta

Abstract: Novel regenerative therapies may stem from deeper understanding of the mechanisms governing cardiovascular lineage diversification. Using enhancer mapping and live imaging in avian embryos, and genetic lineage tracing in mice, we investigated the spatio-temporal dynamics of cardiovascular progenitor populations. We show that expression of the cardiac transcription factor Nkx2.5 marks a mesodermal population outside of the cardiac crescent in the extraembryonic and lateral plate mesoderm, with characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 86 publications
1
27
0
Order By: Relevance
“…A long-unanswered question is whether each of these transient hematopoieses is essential for the embryonic growth. Hemogenic endocardial cells arise in the developing heart tube and contribute to transient hematopoiesis including primitive erythroid and transient definitive progenitors (Nakano et al, 2013;Yzaguirre and Speck, 2016;Zamir et al, 2017). This endocardial hematopoiesis is dependent on a homeobox transcription factor, Nkx2-5 (also known as tinman in Drosophila), suggesting that they are the mammalian homologs of tinman-dependent hematopoiesis in Drosophila (Han and Olson, 2005;Mandal et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A long-unanswered question is whether each of these transient hematopoieses is essential for the embryonic growth. Hemogenic endocardial cells arise in the developing heart tube and contribute to transient hematopoiesis including primitive erythroid and transient definitive progenitors (Nakano et al, 2013;Yzaguirre and Speck, 2016;Zamir et al, 2017). This endocardial hematopoiesis is dependent on a homeobox transcription factor, Nkx2-5 (also known as tinman in Drosophila), suggesting that they are the mammalian homologs of tinman-dependent hematopoiesis in Drosophila (Han and Olson, 2005;Mandal et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Another equally plausible hypothesis is that a group of cells exist within the pool of CM 478 progenitors which possess alternative potential to become the blood or vascular lineage. Numerous 479 evidences from mouse studies suggested the presence of bipotential cardiac progenitor populations 480 which co-expressed cardiac and hematopoietic markers in the developing heart tube (Caprioli et al 481 2011;Nakano et al 2013;Zamir et al 2017). The presence of hematopoietic markers in our 482 experiment therefore suggests the presence of such cells in zebrafish and that, similar to mammals, the 483 hematopoietic cell fate is suppressed with the progression of CM differentiation, a process which 484 occurs between linear heart tube formation and chamber differentiation.…”
mentioning
confidence: 99%
“…Furthermore, in silico analysis predicts that the combined activity of both P53 and β-catenin activated by 10 mM Li + could target many genes related to mesodermal lineages differentiation (Figure 2c) and HE development ( Figure S9). Even though Nkx2-5 is a master regulator of cardiogenesis 26 , its expression has also been found in hemogenic endothelial cells 25 . In silico analysis also predicted that the P53 activation by 10 mM Li + 18 could hinder the development of mature HE cells because of the transcriptional inactivation of Runx1 (Figure 2c), which is essential for the development of HSC precursors from HE cells 27,28 .…”
Section: Discussionmentioning
confidence: 99%